Dynamic equilibria in supported ionic liquid phase (SILP) catalysis: in situ IR spectroscopy identifies [Ru(CO)xCly]n species in water gas shift catalysis. Issue 1 (5th December 2017) - Bauer, Tanja; Stepic, Robert; Wolf, Patrick; Kollhoff, Fabian; Karawacka, Weronika; Wick, Christian R.; Haumann, Marco; Wasserscheid, Peter; Smith, David M.; Smith, Ana-Sunčana; Libuda, Jörg
Abstract : Ru-based SILP systems efficiently catalyze the low-temperature water-gas shift reaction (WGSR). Abstract : Ru-based supported ionic liquid phase (SILP) systems efficiently catalyze the low-temperature water-gas shift reaction (WGSR). While previous studies suggest that Ru-carbonyl species play an important role in the mechanism, detailed knowledge on the catalytically active species is still missing. To identify these carbonyl complexes, we apply in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) in combination with density functional theory (DFT). Investigations of an as-prepared [Ru(CO)3 Cl2 ]2 /[C4 C1 C1 Im]Cl/Al2 O3 catalyst indicate splitting of the dimer induced by Cl − . Subsequently, an equilibrium between several [Ru(CO) x Cl y ] n species is established, in which the IL serves as an effectively infinite Cl − reservoir. We find that the major species in the system freshly-prepared from [Ru(CO)3 Cl2 ]2 is indeed [Ru(CO)3 Cl3 ] − . A smaller amount of [Ru(CO)2 Cl3 ] − and chloride-rich species [Ru(CO)2 Cl4 ] 2− or [RuCOCl4 ] 2− are also found in the SILP. Similar Ru-carbonyl species are observed during carbonylation of RuCl3 /[C4 C1 C1 Im]Cl/Al2 O3, another potential WGSR catalyst. The response of [Ru(CO)3 Cl2 ]2 /[C4 C1 C1 Im]Cl/Al2 O3 to heating and/or CO dosing was probed in situ and the results confirm the presence of the equilibrium proposed above.